Polydopamine-Bridged Synthesis of Ternary h-BN@PDA@TiO2 as Nanoenhancers for Thermal Conductivity and Flame Retardant of Polyvinyl Alcohol - Wang, Xiaodong; Hu, Weizhao; Hu, Yuan (Frontiers in Chemistry, 2020)
In this study, h-BN@PDA@TiO2 hybrid nanoparticles were prepared and used as functional fillers to prepare PVA nanocomposites, and the effects of hybrid particles on PVA thermal conductivity and flame retardant properties were studied. The results showed that hybrid particles could significantly improve the thermal conductivity and flame retardant performance of PVA composites, and effectively inhibit the release of toxic gases such as combustible pyrolysis products and CO, which enhanced the fire safety of PVA composites. When the addition amount of hybrid particles is 5 wt%, the thermal conductivity of PVA composites is 239.1% higher than that of the pure PVA and the corresponding temperature of PVA composites with a mass loss of 5 wt% was 16.2 ℃ higher than that of the pure PVA. This is due to the barrier effect of h-BN and the protective effect of dense carbon layer catalyzed by TiO2.